Is Acquired Disgust More Difficult to Extinguish Than Acquired Fear? an Event-Related Potential Study - Zeng, Qing; Lv, Lishan; Zheng, Xifu (Frontiers in Psychology, 2021)
This study used the classical conditioned acquisition and extinction paradigm to compare which of two emotions, acquired disgust or acquired fear, was more difficult to extinguish, based on behavioral assessments and the ERP technique. Behavioral assessments revealed that, following successful conditioned extinction, acquired disgust was more difficult to extinguish. The ERP results showed that, at the early stage of P1, the amplitude of conditioned fear was significantly smaller than that of conditioned disgust, and both were significantly different from the amplitude under neutral conditions; at the middle stage of N2, the difference between the amplitudes of conditioned disgust and conditioned fear disappeared, but they were still significantly different from the amplitudes of conditioned neutral stimuli; at the late stage of P3, the difference between conditioned disgust and conditioned neutral stimuli disappeared, but the difference between conditioned fear and neutral stimuli remained, suggesting that in terms of how the brain works, acquired fear was more difficult to extinguish than acquired disgust.